Liquefied Petroleum Gas (LPG) Supply Scenarios from a System Dynamics Approach - Adaniya Higa, Beatriz Juana (2023)
In this paper we analyze the problems of LPG supply in Peru, based on various factors that have a significant impact on its value chain. The complexity of the analysis requires the use of various techniques and methodologies, such as the system dynamics used in this study, which, using a proposed model, generates various hypotheses to explain the behavior patterns of the analyzed variable and to understand causal logic over time when it interacts with other variables. As a result, a model that generates possible scenarios that confirm the decrease in LPG production over time due to inaction with respect to natural gas production, and highlights the need to encourage investments in exploration efforts to further increase natural gas reserves, is proposed. The research concludes that it is necessary to establish public policies to achieve market conditions that ensure LPG supply.